Analysis of The Effectiveness of Pbg Licensing Services at The Dpmptsp Office of Bulukumba Regency, South Sulawesi Province - Rahmat Darmawan; Herman H; Haerul; Andi Anugrah Mahyuddin (International Journal Of Public Policy and Bureaucracy, 2026)
This study aims to analyze the effectiveness of Building Approval (PBG) services following the implementation of Government Regulation No. 16 of 2021 and to identify the factors that influence service effectiveness. The research focuses on two main questions: first, how effective PBG services are in terms of goal attainment, efficiency, responsiveness, accountability, and public satisfaction; and second, what factors determine this effectiveness, particularly those related to service quality based on the SERVQUAL dimensions. The study was conducted at the Investment and One-Stop Integrated Service Office (DPMPTSP) in Kabupaten Bulukumba using a qualitative case study approach. The findings indicate that the effectiveness of PBG services has not yet reached an optimal level. Although regulatory frameworks and service procedures have been formally established, several challenges remain, including complex coordination among local government agencies, variations in service completion times, uneven distribution and competence of human resources, and the limited integration of digital systems such as OSS-RBA and SIMBG. From the perspective of service quality, the dimensions of reliability, responsiveness, and assurance emerge as the dominant factors influencing service effectiveness. Meanwhile, limitations in service facilities and applicants’ digital literacy also affect the overall service experience. The study concludes that the effectiveness of PBG services is shaped by the alignment between service process quality, institutional capacity, cross-sector governance, and digital system support. Strengthening cross-unit SOPs and service level agreements, improving staff competencies, optimizing system integration, and enhancing communication and applicant assistance are therefore necessary to achieve effective, accountable, and public value–oriented PBG services.